SIKAP KEPEMIMPINAN SIMSON ATAS BANGSA ISRAEL DAN RELEVANSINYA PADA KEPEMIMPINAN KAUM RELIGIUS - Marianus Elki Semit; Gregorius Tri Wardoyo (Program Studi Filsafat Universitas Katolik Widya Mandira Kupang, 2023)
The focus of this paper explores Samson's leadership towards the Israelites and its relevance to the leadership of the religious people today. His leadership became a storehouse of knowledge for humans today. His loyalty to God became the basis for success in leading the Israelites. His shrewdness in fighting the Philistines was extraordinary but in the end he also fell into the hands of the Delilah. His desire was too strong to be able to control himself. The tendency to use feelings over reason so that in the end Samson fell for the seduction of death. Samson's carelessness brought disaster upon himself. The purpose of this writing is to open the horizons of thinking about leadership that prioritize peace and justice in living together. The author in this paper uses a literature review. The author finds something new from Judge Samson's leadership attitude, namely Samson's carelessness. Samson did not listen to God, he listened more to his heart out of love for Gentile women. The author suggest that we have to think critically before acting, don't let what is decided because it is based on the desires of the flesh that bring disaster to oneself.